A normative study of cervical range of motion measures including the flexion–rotation test in asymptomatic children: side-to-side variability and pain provocation. (7th August 2016) - Budelmann, Kim; Piekartz, Harry von; Hall, Toby
Abstract : Objectives: Cervical movement impairment has been identified as a core component of cervicogenic headache evaluation. However, normal range of motion values in children has been investigated rarely and no study has reported such values for the flexion–rotation test (FRT). The purpose of this study was to identify normal values and side-to-side variation for cervical spine range of motion (ROM) and the FRT, in asymptomatic children aged 6–12 years. Another important purpose was to identify the presence of pain during the FRT. Methods: Thirty-four asymptomatic children without history of neck pain or headache (26 females and 8 males, mean age 125.38 months [SD 13.14]) were evaluated. Cervical spine cardinal plane ROM and the FRT were evaluated by a single examiner using a cervical ROM device. Results: Values for cardinal plane ROM measures are presented. No significant gender difference was found for any ROM measure. Mean difference in ROM for rotation, side flexion, and the FRT were less than one degree. However, intra-individual variation was greater, with lower bound scores of 9.32° for rotation, 5.30° for side flexion, and 10.89° for the FRT. Multiple linear regression analysis indicates that movement in the cardinal planes only explains 19% of the variance in the FRT. Pain scores reported following the FRT were less than 2/10. Discussion: Children have consistently greater cervical spine ROM than adults. In children, side-to-side variation in rotation and side flexion ROM and range recorded during the FRT indicates that the clinician should be cautious when using range in one direction to determine impairment in another. Range recorded during the FRT is independent of cardinal movement variables, which further adds to the importance of the FRT, as a test that mainly evaluates range of movement of the upper cervical spine.